2017
DOI: 10.1080/17460441.2017.1367281
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the use ofXenopusfor successful drug screening

Abstract: Understanding embryogenesis currently relies largely on the control of gene expression via several signaling pathways. Many of the embryonic signaling pathways guiding embryological events are implicated in diseases that lack effective cure or treatment. Because of the large number and size of the eggs, the rapid development of the embryos and the fact they are amenable to pharmacological, surgical and genetic techniques, Xenopus laevis has been successfully used in searching for compounds that target embryoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 43 publications
0
7
0
2
Order By: Relevance
“…The commonness of neural tube defects during pregnancies [19] stresses the importance of this topic. The fact that Xenopus has recently become of interest for high-content screening [24] further supports the relevance of this proof of concept, especially as ALMOST could as well be integrated into robotic workflows. For the quantitative measurements of complex features on the embryo, a coordinate system like it has been developed for spherical embryos [25] or other frameworks for modeling embryogenesis [26] could be applied.…”
Section: Discussionmentioning
confidence: 82%
“…The commonness of neural tube defects during pregnancies [19] stresses the importance of this topic. The fact that Xenopus has recently become of interest for high-content screening [24] further supports the relevance of this proof of concept, especially as ALMOST could as well be integrated into robotic workflows. For the quantitative measurements of complex features on the embryo, a coordinate system like it has been developed for spherical embryos [25] or other frameworks for modeling embryogenesis [26] could be applied.…”
Section: Discussionmentioning
confidence: 82%
“…2e, f). Taking together, these results show that death after infection-surgery occurs sequentially over the time, as a direct consequence of increased weakness, and it does not happen at the first immediate hours after surgery (st. [26][27][28][29][30]. Interestingly, this analysis also shows that the peak of death in absence of brain Brain signaling does not affect primitive myeloid precursors Next, we asked whether the protective effects of the brain were due to action on the development of the primitive immune system (regardless of infection, as it does with muscle and nerve development) or whether, conversely, the brain acted on the active response to infection (implying differences between Control and BRanimals only after infection).…”
Section: Early Brain Protects Against the Infection-induced Apoptosismentioning
confidence: 95%
“…We developed a Xenopus model in which we could study braindependent events in embryogenesis: the brain is removed during early embryonic stages, but the animal can be kept alive and development continues. The ability of this vertebrate, a popular model for numerous biomedical contexts, [27][28][29][30][31][32][33][34] to survive and develop without a brain provides a unique opportunity to understand the role of the brain in diverse systems-level outcomes. Our prior research into brain-dependent developmental signaling revealed that the nascent brain, even before being fully formed, plays an instructive role in patterning somitic muscle and peripheral neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we investigated if this inhibitory effect is also observed in vivo. Manipulation of Xenopus laevis embryonic development has been successfully used to validate compounds targeting Wnt/β-catenin signaling through the interpretation of embryonic phenotypes and Wnt signaling overactivation [11]. In this context, injection of 1.6 pmol lonchocarpin in the embryo animal dorsal blastomeres ( Figure 3A) induced head defects, characterized by reduction of anterior structures in 23% of injected embryos, such as the cement gland and diminished eyes ( Figure 3D) while uninjected or DMSO-injected embryos developed normally ( Figure 3B,C).…”
Section: Lonchocarpin Treatment Disturbs Xenopus Laevis Embryos Axialmentioning
confidence: 99%